2022
DOI: 10.3390/tropicalmed7120421
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Alcoholic Cirrhosis and Non-Alcoholic Steatohepatitis Cirrhosis Outcomes among Hospitalized Patients in the United States: Insight from National Inpatient Sample Database

Abstract: Patients with co-morbidities like cirrhosis are at risk of worse outcome from COVID-19 infection. Given limited prior studies, we evaluated outcomes associated with COVID-19 infection in alcoholic and non-alcoholic steatohepatitis cirrhotic (CC+) versus cirrhotic without COVID-19 (CC−). We performed retrospective analysis of 822,604 patients including 28,610 COVID-19 patients from the National Inpatient Sample database with alcoholic and NASH cirrhosis enrolled between 1 January 2020 to 31 December 2020, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Additionally, elevated aminotransferase levels at the time of admission also correlate with higher mortality [ 2 , 18 ]. Patients with underlying chronic liver disease were of particular interest, as patients with cirrhosis were noted to have worse outcomes with concomitant SARS-CoV-2 infections [ 1 , 2 , 16 , 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, elevated aminotransferase levels at the time of admission also correlate with higher mortality [ 2 , 18 ]. Patients with underlying chronic liver disease were of particular interest, as patients with cirrhosis were noted to have worse outcomes with concomitant SARS-CoV-2 infections [ 1 , 2 , 16 , 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 infection is associated with a variety of gastrointestinal manifestations. Patients with cirrhosis are particularly interesting, as there is emerging data that cirrhotic patients have an increased mortality rate with SARS-CoV-2 [ 1 ]. Mortality rates have also been noted to increase in patients with decompensated cirrhosis (when compared to compensated disease) and increase with the rising Model for End-Stage Liver Disease (MELD) score or Child–Pugh classification.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of COVID-19 on STEMI ( 32 ) and stoke ( 33 ) outcomes have also been demonstrated, resulting in higher in-patient mortality, length of stay and cost of hospitalization. Kapuria et al found that patients with COVID-19 and cirrhosis had 3 times higher mortality than those without COVID-19 ( 34 ) and Pal et al found sex and racial disparities in hospitalizations and in rates of adverse outcomes ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because of its worldwide significance and potential complications, ALD is often considered as a condition that might be exacerbated in the course of various newly developed medical conditions [198]. Infection with SARS-CoV-2 is the ideal example of such occurrences [199][200][201]. Of note, according to a meta-analysis, since the beginning of COVID-19 pandemic, ALD has been indicated as the most common reason for listing for and the fastest increasing cause of liver transplantation (LT) [202].…”
Section: Ethanol Liver and Covid-19-a Global Perspectivementioning
confidence: 99%